On $L^1$-approximation of Trigonometric Series - Leindler, Laszlo (Journal of Informatics and Mathematical Sciences, 2010)
In the paper [3] we defined three new classes of sequences motivated by the Logarithm Rest Bounded Variation Sequences defined by S.P. Zhou [4]. By means of these classes we extended Zhou's theorems pertaining to $L^1$-convergence of sine series. Very recently R.J. Le and S.P. Zhou [1] proved $L^1$-approximation theorems. Now we generalize their theorems to our wider classes.